Formulation and Stability Test of HPMC and Carbomer 940 based-Gel Formulation Containing Plantago major L. hydroalcoholic extract - Khafi, Muhammad; Hertiani, Triana; Murwanti, Retno; Bayu Irawan, Muhamad; Marzuki, Ahmad; Dwi Salim, Rozin (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
The P. major plant has long been utilized in traditional herbal medicine and is widely accessible in Indonesia and globally. Extensive research has demonstrated its efficacy in wound healing through both clinical and preclinical studies. Gel formulations are recognized for establishing a conducive moist environment essential for wound healing, thus rendering them suitable for topical wound treatment. This study assesses the stability of HPMC gel base, carbomer 940, and their combination as carriers for the ethanol extract of P. major leaves. Stability testing involved a freeze-thaw cycle test at temperatures of 4°C and 40°C for three cycles. The findings indicate no significant alteration in the organoleptic properties and pH of the gel formulations before and after stability testing. However, t-test analysis reveals a noteworthy decrease in viscosity for carbomer and its combination, albeit not for HPMC alone. In conclusion, HPMC exhibits superior stability as a gel base compared to Carbomer 940 and their combination.